PROGNOSTIC SIGNIFICANCE OF MET235/235THR POLYMORPHISMS OF GENE AGT FOR DEVELOPMENT OF CARDIOVASCULAR DISORDERS IN PROFESSIONAL SPORTSMEN - D. V. Muzhenya; A. R. Tuguz; T. M. Ashkanova; A. R. Pshidatok; I. V. Smolkov; D. S. Shumilov (Российский кардиологический журнал)
Aim. Assessment of Met235Thr polymorphisms of gene AGT, related to cardiovascular diseases (CVD), as early genetic predictors of occupational diseases in professional sportsmen in Adyghea Republic (AR).Material and methods. Dispersion of Met235/235Thr polymorphic variants of AGT gene studied via SNP-method (single nucleotide polymorphism) with allele-specific primers and electrophoretic detection of results (NPF “Litech”). С704Т polymorphisms of gene AGT (rs699) with replacements of cytosine by thymine at 704 position of gene, and methionine by threonine (Met>Thr) at 235 aminoacid consequence of angiotensine, were typed in the specimens of genomic DNA of professional sportsmen (n=40), donors (n=120) and CVD patients (n=64) aged 23-65 y. o., from two ethnicities — Adyges and Russians. Experimental findings were analized with relevant statistical software (SPSS Statistics 17.0).Results. Prevalence of 235Thr allele and Thr235Thr genotype of AGT is significantly higher in the group of patients comparing to healthy controls (р=0,05, χ2=5,84; р=0,01, χ2=6,2) and sportsmen (р=0,05, χ2 =6,15; р=0,02, χ2=5,04). High risk of CVD development in carriers of allele 235Thr variant (OR=4,34) as Thr235Thr mutation genotype (OR=3,89), caused by the increase of agiotensine level in blood plasma, confirms its association with the diseases of cardiovascular continuum (DCC) in AR inhabitants. Under conditions of intensive physical exertion the Thr235Thr genotype of qualified sportsmen is an adverse factor leading to cardiovascular pathology.Conclusion. The new data obtained, on the increased incidence of prognostically adverse Met235/235Thr polymorhpism of the gene AGT for CVD in professional sportsmen, can be applied for early molecular and genetic predictors of cardiovascular disorders at individual level, as for defining of risk groups with further correction of training schedule.